Count all her bones - Henry, April (Christy Ottaviano Books, Henry Holt and Company, 2017)
Six months ago Griffin accidentally carjacked Cheyenne, who is blind. He helped her escape from his father, who planned to hold Cheyenne for ransom. When Griffin goes missing right before he's set to testify at his father's trial, Cheyenne sets out to save him from his father's henchmen. But is Griffin a pawn or a player in this deadly affair?